Effect of different type of soil in efficiency of thermal reduction in earth air heat exchanger (EAHE) - Nor Azliza, Jamili (2016)
This thesis tried to examine if different type of soil used in Earth Air Heat Exchanger (EAHE) can affect the temperature reduction of the air. EAHE is a passive cooling system that can provide cooled air without consuming a lot of electrical energy. EAHE consist of a connected pipe buried under ground at 1 meter depth and 23.2 meter length. The pipe connection needs to have an inlet and an outlet. Detector was placed to suck in the air. Air went through the pipe under the ground and heat transfer happened. The heat would transferred to the pipe by conduction and then to the soil. Different soil has different properties. This study is to determine which soil can reduce more temperature. Two soils were considered namely, sand and crushed aggregate soil. The soil was placed around the pipe under the ground before the hole was filled back with the sand. Properties of the soil such as specific gravity, particle size analysis and thermal diffusivity were tested in the laboratory. At the end of the study, the results indicated that a maximum temperature reduction of 5.3°C was achieved when the pipe was surrounded by the sand. The properties of sand gave the most thermal reduction to the air flow inside the pipe if EAHE system was installed. Particle size of sand was smaller. Smaller particle size had a large surface area. Number of surface area can helped in transferring the heat from air to the pipe and to the soil used. Water content also effects the temperature reduction of the air. Higher moisture content of the soil was proved to reduce the temperature reading of the air came out from the outlet. Thermal diffusivity also one of the soil properties which can affect the heat reduction of EAHE system. High thermal diffusivity helped in transmitting the heat and cooling the air inside the pipe. The result concluded that, soil with large surface are, high water content and high thermal conductivity can reduce the temperature of the air that went through the pipe and produce cooler air to the outlet.